Loss of transforming growth factor counteraction on interleukin 1 mediated effects in cartilage of old mice. Issue 12 (1st December 2002) - Scharstuhl, A; van Beuningen, H M; Vitters, E L; van der Kraan, P M; van den Berg, W B
Abstract : Objective: To investigate if a difference exists between young and old mice in the response of articular cartilage to interleukin 1 (IL1) and transforming growth factor β (TGFβ) alone or in combination. Methods: The interaction of IL1 and TGFβ was studied in cartilage of young (three months) and old mice (18 months) both in vivo and in vitro. Therefore, IL1, TGFβ, or IL1 together with TGFβ was injected into the knee joints of mice on days 1, 3, and 5 before harvest of the patellae on day 6. Alternatively, isolated patellae were stimulated with IL1, TGFβ, or IL1 together with TGFβ in culture for 48 hours. Proteoglycan (PG) synthesis and nitric oxide (NO) production were measured. Results: IL1 inhibited PG synthesis and increased NO production in cartilage of both young and old mice. On the other hand, TGFβ stimulated PG synthesis and reduced NO production in both age groups. Importantly, TGFβ was able to counteract IL1 mediated effects on PG synthesis and NO production in young but not in old mice. Conclusions: Contrary to the findings in young mice, the cartilage of old animals does not antagonise IL1 effects via TGFβ. This loss of responsiveness to the pivotal cytokine TGFβ on effects of IL1 can be important in the initiation and progression of osteoarthritis (OA).